La culture autochtone est-elle soluble dans la forme scolaire ? Réflexions à partir de quelques expériences pédagogiques (Hawai'i, Nouvelle-Calédonie) - Marie Salaün (Les éditions de la Maison des sciences de l'Homme, 2016)
For the past 40 years, Indigenous activists throughout the world have harshly criticized the persistence of « Colonial Education ». Indigenous students neither succeed in europeocentric schools, nor do they manage to reintegrate into their communities with the required traditional knowledge. The implementation of vernacular languages and cultures in formal schooling is today considered to be the best way to redress the colonial wrongs and achieve educational justice. Nonetheless, the process bears risks. When indigenous knowledge is formally taught - dramatically transforming its mode of transmission - what impact does this have? And what impact does this integration have on school as an institution, when it is expected to fulfill what constitutes a radically new mission? These questions will be addressed through empirical case studies from Oceania: the stakes of using 'Ōlelo Hawai'i as a medium of instruction in Hawaii's immersion schools and the teaching of Kanak languages and culture in New Caledonian elementary schools.